2022
DOI: 10.3390/su142215424
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Acceptance and Preference for Camel Milk in Selected European and Mediterranean Countries

Abstract: In this paper, we analyse consumer acceptance, preferences and attitudes to camel milk based on a cross-country study based on qualitative focus groups with consumers. Outside the main consumption countries where camel milk is a regular part of the daily diet, many consumers buy this product primarily due to its promised health benefits. Furthermore, they are willing to pay a substantial price premium for camel milk. The findings from the literature study suggest the need for further research aimed at improvin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…(Mihic et al, 2016) qui donne lieu à une pléthore de revues scientifiques contestables largement relayées par les médias, quelques travaux menés in vitro, voire in vivo, plus rarement dans des essais cliniques, ont ouverts des pistes de compréhension des mécanismes derrière les effets relatifs à la régulation de la glycémie, au contrôle de la croissance des cellules tumorales, aux propriétés antioxydantes ou à l'allègement des symptômes de l'autisme (Ashraf et al, 2021 ;Oussaief et al, 2020 ;Bashir et Al-Ayadhi, 2014 ;Gahlot, Adams, 2023). La recherche de la part des consommateurs, d'un produit à la réputation bénéfique pour la santé, explique sans doute la croissance de la demande en milieu urbain, non seulement dans les pays originaires des grands camélidés, mais également dans les pays occidentaux (Profeta et al, 2022).…”
Section: ■ Du Lait De Chamelle Pasteurise Dans Les Grandes Surfaces D...unclassified
“…(Mihic et al, 2016) qui donne lieu à une pléthore de revues scientifiques contestables largement relayées par les médias, quelques travaux menés in vitro, voire in vivo, plus rarement dans des essais cliniques, ont ouverts des pistes de compréhension des mécanismes derrière les effets relatifs à la régulation de la glycémie, au contrôle de la croissance des cellules tumorales, aux propriétés antioxydantes ou à l'allègement des symptômes de l'autisme (Ashraf et al, 2021 ;Oussaief et al, 2020 ;Bashir et Al-Ayadhi, 2014 ;Gahlot, Adams, 2023). La recherche de la part des consommateurs, d'un produit à la réputation bénéfique pour la santé, explique sans doute la croissance de la demande en milieu urbain, non seulement dans les pays originaires des grands camélidés, mais également dans les pays occidentaux (Profeta et al, 2022).…”
Section: ■ Du Lait De Chamelle Pasteurise Dans Les Grandes Surfaces D...unclassified
“…It can be concluded that the inability to identify adulteration of raw camel's milk by low quantities of cow's milk may be attributed to the milk's unique organoleptic properties, which differ from those of cow's milk. Indeed, camel's milk has a normal odor, an opaque white color that can be attributed to the low carotene content, and homogenized fat facts which gives the milk a smooth appearance (Ahmed et al, 2014), and a more salty taste (which can vary based on the diet of the animal) compared to that of cow's milk (Profeta et al, 2022;Singh et al, 2017). The intensity of these characteristics can therefore hide low amounts of added cow's milk.…”
Section: Spectrum Analysismentioning
confidence: 99%
“…Furthermore, the analysis indicated that education was the sole component that significantly influenced consumer awareness of camel milk. In their recent study, Profeta et al (2022) conducted a qualitative analysis to examine the consumer acceptance, preferences, and attitudes towards camel milk. The study employed a cross-country approach, involving participants from five different countries.…”
Section: Literature Reviewmentioning
confidence: 99%